Inclusive Strategy for Small and Marginal Farmers in Tapioca Production, Processing and Marketing - Sendilkumar, R; Arya, S (Journal of Agricultural Extension Management, 2018)
This study was conducted to explore the post-harvest value additionopportunities tapioca, identify the constraints faced by small and marginalfarmers in processing and to suggest a strategy. Primary data from 60 tapiocafarmers of Elamadu Grama Panchayath of Kollam district, Kerala werecollected through interview schedule. Expert opinion was collected from theScientists of Kerala Agricultural University (KAU), KVK, and CTCRI etc.to screen the appropriate technology for tapioca value addition. The dataobtained were analysed using percentage analysis, SWOC and COWS analysis.It was found that a number of farmers were involved in tapioca cultivation andcould produce marketable surplus, but were not engaged in any post-harvestvalue addition activities. Indeed, farmers have expressed their willingness tostart value addition jointly as a group. The technocrats opined that tapiocasnacks and chips are better options for value addition at farm level. The studyhighlighted the need for an exclusive organisation for tapioca cultivation,marketing and processing. Initiating farmer driven producer organisationsand consumer linked value chain would be a promising strategy for livelihoodof small and marginal farmers of tapioca.